Work engagement among post-millennial generation in Jakarta: Examining work-life balance and work values dynamics - Nursanti, Tinjung Desy; Lestari, Fidya (Universitas Tarumanagara, 2024)
Employers must increase work engagement to keep workers actively involved, committed, and making the greatest contributions to the business. Encouraging employee well-being through work-life balance and work values is one way to increase work engagement. This research aims to examine the influence of work-life balance and work value on work engagement among Generation of post-millennial in Jakarta city. The research method used to analyze this study is quantitative with a descriptive format aimed at explaining and summarizing various conditions and situations. The research method employed partial hypothesis testing using the SmartPLS program. The sample size for this study is 150 respondents and data collection are done through questionnaires. The data analysis techniques and tools used in this study include descriptive statistics, inner model testing, and outer model testing. The population of this study is the post-millennial generation workers, and they also serve as the sample for the study. The research results indicate that work-life balance has a positive and significant impact on work engagement, work value has a positive and significant impact on work engagement, and both work-life balance and work value have a positive and significant influence on work engagement among the post-millennial generation in Jakarta city. Perusahaan harus berupaya untuk terus meningkatkan keterlibatan kerja agar pekerja tetap aktif, berkomitmen, dan memberikan kontribusi terbesar bagi bisnis. Mendorong kesejahteraan karyawan melalui keseimbangan kehidupan kerja dan nilai-nilai kerja merupakan salah satu cara untuk meningkatkan keterlibatan kerja. Penelitian ini bertujuan untuk menguji pengaruh work-life balance dan work value terhadap work engagement pada generasi pasca milenial atau generasi Z di kota Jakarta. Metode penelitian yang digunakan adalah kuantitatif deskriptif yang bertujuan untuk menjelaskan dan merangkum berbagai kondisi dan situasi. Selain itu, dilakukan pengujian hipotesis secara parsial dengan menggunakan program SmartPLS. Besar sampel penelitian ini adalah 150 responden, dan pengumpulan data dilakukan melalui distribusi kuesioner. Teknik dan alat analisis data yang digunakan dalam penelitian ini meliputi statistik deskriptif, pengujian inner model, dan pengujian outer model. Populasi penelitian ini adalah pekerja yang termasuk dalam kategori generasi pos-milenial dan mereka juga dijadikan sebagai sampel penelitian. Hasil penelitian menunjukkan bahwa work-life balance berpengaruh positif dan signifikan terhadap work engagement, nilai kerja berpengaruh positif dan signifikan terhadap work engagement, serta work-life balance dan work value mempunyai pengaruh positif dan signifikan terhadap work engagement generasi pasca milenial di kota Jakarta.